Genetic potential for residual feed intake and diet fed during early- to mid-gestation influences post-natal DNA methylation of imprinted genes in muscle and liver tissues in beef cattle. (15th May 2021) - Devos, Julia; Behrouzi, Amir; Paradis, Francois; Straathof, Christina; Li, Changxi; Colazo, Marcos; Block, Hushton; Fitzsimmons, Carolyn
Abstract: Discovery of epigenetic modifications associated with feed efficiency or other economically important traits would increase our understanding of the molecular mechanisms underlying these traits. In combination with known genetic markers, this would provide opportunity to improve genomic selection accuracy in cattle breeding programs. It would also allow cattle to be managed to improve favorable gene expression. The objective of this study was to identify variation in DNA methylation between beef cattle of differential pre-natal nutrition and divergent genetic potential for residual feed intake (RFI). Purebred Angus offspring with the genetic potential for either high (HRFI) or low (LRFI) RFI were prenatally exposed to either a restricted maternal diet of 0.5 kg/d average daily gain (ADG) or a moderate maternal diet of 0.7 kg/d ADG from 30 to 150 d of gestation. We performed DNA methylation analysis of differentially methylated regions (DMR) of imprinted genes (Insulin-like growth factor 2 ( IGF2 ) DMR2, IGF2 / H19 imprinting control region (ICR) and IGF2 receptor ( IGF2R ) DMR2) using post-natal samples of longissimus dorsi (LD) muscle taken from male and female calves at birth and weaning, and of LD muscle, semimembranosus (SM) muscle, and liver samples collected from steers at slaughter (17 months of age). Interestingly, for all three DMR investigated in liver, LRFI steers had higher levels of methylation than HRFI steers. In LD muscle, IGF2 / H19 ICR methylation differences for heifers at birth were due to pre-natal diet, while for steers at birth they were mostly the result of genetic potential for RFI with LRFI steers again having higher levels of methylation than HRFI steers. While results from repeated measures analysis of DNA methylation in steers grouped by RFI revealed few differences, in steers grouped by diet, we found higher methylation levels of IGF2 DMR2 and IGF2R DMR2 in LD muscle of restricted diet steers at weaning and slaughter than at birth, as well as increased methylation in LD muscle of restricted diet steers compared with moderate diet steers at weaning and/or slaughter. Our results suggest that differential pre-natal nutrition, and divergent genetic potential for RFI, induces tissue- and sex-specific alterations in post-natal IGF2 and IGF2R methylation patterns and that these patterns can vary with age in Angus beef cattle.